2013
DOI: 10.1111/jdi.12141
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Lactobacillus casei strain Shirota affects autonomic nerve activities in a tissue‐specific manner, and regulates glucose and lipid metabolism in rats

Abstract: Aims/Introduction: Previously, it was observed that long-term ingestion of a probiotic strain Lactobacillus casei Shirota (LcS) ameliorates insulin resistance and glucose intolerance in rats fed a high-fat diet. In the present study, we examined its possible role in the autonomic nervous system during LcS-induced modulations in glucose and lipid metabolism or cardiovascular functions. Materials and Methods: The present study examined the effects of intragastric (IG) LcS injection on autonomic nerve tones in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
(42 reference statements)
3
31
0
Order By: Relevance
“…The pathway analysis of the 179 stress-responsive genes showed that the academic examination preferentially affected a group of genes related to lipid metabolism (e.g., ERCC2, FGF1, PPARGC1A, RARA, SREBF1). Interestingly, our previous study revealed that L. casei strain Shirota attenuated lipid metabolism via suppression of sympathetic nerve activity (41). The L. casei strain Shirota admin-istration prevented the additional changes in gene expression levels, including those of lipid metabolism-related genes (ERCC2, FGF1, PPARGC1A).…”
Section: Discussionmentioning
confidence: 90%
“…The pathway analysis of the 179 stress-responsive genes showed that the academic examination preferentially affected a group of genes related to lipid metabolism (e.g., ERCC2, FGF1, PPARGC1A, RARA, SREBF1). Interestingly, our previous study revealed that L. casei strain Shirota attenuated lipid metabolism via suppression of sympathetic nerve activity (41). The L. casei strain Shirota admin-istration prevented the additional changes in gene expression levels, including those of lipid metabolism-related genes (ERCC2, FGF1, PPARGC1A).…”
Section: Discussionmentioning
confidence: 90%
“…Earlier studies demonstrated that vagal pathways innervating the gastrointestinal tract, pancreas, and liver are involved in the control of assimilation, storage, mobilization, conversion, and oxidation of macronutrients [75, 76]. Lactobacillus has been hypothesized to modulate fat metabolism via a vagal-dependent pathway [77] and vagal ablation abolished -ornithine positive effects on lipid metabolism [78]. PPARγ signaling in NG has notably been hypothesized to regulate diet-driven thermogenesis [79].…”
Section: Resultsmentioning
confidence: 99%
“…The afferent autonomic reflex in abdominal organs plays an important role in sensing various nutritional components that arrive in the gastrointestinal tract and for sending information to the central nervous system for regulating efferent autonomic nerves (Tanida et al, 2014;Tanida and Satomi, 2011). We previously found that IG injections of Lactobacillus (Tanida et al, 2014) or monosodium glutamate (Tanida and Satomi, 2011) affected efferent autonomic nerve discharges through the afferent vagal nerve in the digestive organs because efferent sympathetic responses to these agents were abolished in rats treated vagal nerve denervation (Tanida et al, 2014;Tanida and Satomi, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…We previously found that IG injections of Lactobacillus (Tanida et al, 2014) or monosodium glutamate (Tanida and Satomi, 2011) affected efferent autonomic nerve discharges through the afferent vagal nerve in the digestive organs because efferent sympathetic responses to these agents were abolished in rats treated vagal nerve denervation (Tanida et al, 2014;Tanida and Satomi, 2011). In agreement with previous studies, we demonstrated that afferent vagal neurotransmission in the abdominal organs was implicated in the WAT response to l-ornithine, which was similar to the results in our previous reports (Tanida et al, 2014;Tanida and Satomi, 2011). This is a novel finding in that it indicates that l-ornithine ingestion might act on digestive organ sensors and cause a reflex response of the afferent vagal nerve, resulting in increased efferent sympathetic outflows to WAT and BAT through the central nervous system.…”
Section: Discussionmentioning
confidence: 99%